Alternative protein sources in sea bass nutrition - E. D’Agaro (Italian Journal of Animal Science, 2011)
Intensive fish farming profitability is declining word-wide. This situation is mainly due to the extensive reliance on fish meal (FM) as feed ingredient in finfish diets in order to meet the high dietary protein needs. FM quality and prices are variable and its global supply is decreasing and highly dependent on meteoric events (e.g. El niño). Several protein sources are potentially excellent alternatives to FM...